Harold Raymond Wayne Benjamin papers - Benjamin, Harold Raymond Wayne, 1893-1969.; Benjamin, Harold Raymond Wayne, 1893-1969.
Correspondence, speeches, writings, subject file, biographical material, military records, printed matter, photographs, and other papers relating chiefly to Benjamin's career in the field of education. Documents his work in higher education in Latin America and as a consulting editor in the field of education with McGraw-Hill Publishing Company. Family correspondence includes letters to his son, Harold Herbert Benjamin, in which he describes his work as a member of educational study missions to Japan, Afghanistan, Korea, and Latin America. Includes drafts of his book, Sage of Petaluma; Autobiography of a Teacher (1965). Correspondents include Franklin Parker and McGraw-Hill Publishing Company.
Educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Benjamin, Herbert -- Correspondence; Parker, Franklin, -- 1921- -- Correspondence; Benjamin family -- Correspondence; McGraw-Hill Publishing Company -- Correspondence; Education -- Afghanistan; Education -- Korea; Education -- Japan; Education -- Latin America; Afghanistan -- Description and travel; Japan -- Description and travel; Korea -- Description and travel; Latin America -- Description and travel; Educators